1974
DOI: 10.1038/bjc.1974.58
|View full text |Cite
|
Sign up to set email alerts
|

Development of Specific Cell-dependent Antibody During Growth of a Syngeneic Rat Sarcoma

Abstract: Summary.-A micro -cytotoxicity assay was adapted for the detection of cell-dependent antibodies (CDA). Using normal rat spleens as the source of effector cells such CDA activity was readily demonstrable in allo-immune sera tested on cultured sarcoma cells. The same technique was then used to examine for tumour specific antibodies in the sera of Hooded rats bearing a " non-immunogenic " syngeneic metastasizing sarcoma. During the early stages of tumour growth, at Days 7 and 14, tumour specific CDA cytotoxici1y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1975
1975
1978
1978

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Thus tumour immunogenicity could represent an imporant determinant of the degree of K-cell activation in tumourbearing mice. In view of the available evidence that ADCC may be one mechanism in the control of tumour growth (Pollack, 1973;Ortiz de Landazuri et al, 1974;Basham and Currie, 1974;Hersey, 1937;Zighelboim et al, 1974) and of the finding reported here, that mice bearing an immunogenic nonmetastasizing MSV-induced sarcoma show higher levels of K-cell activity than animals inoculated with metastasizing MSV-induced neoplasms, it is tempting to speculate that the degree of K-cell activation may play a role in determining the biological behaviour of experimental tumours.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Thus tumour immunogenicity could represent an imporant determinant of the degree of K-cell activation in tumourbearing mice. In view of the available evidence that ADCC may be one mechanism in the control of tumour growth (Pollack, 1973;Ortiz de Landazuri et al, 1974;Basham and Currie, 1974;Hersey, 1937;Zighelboim et al, 1974) and of the finding reported here, that mice bearing an immunogenic nonmetastasizing MSV-induced sarcoma show higher levels of K-cell activity than animals inoculated with metastasizing MSV-induced neoplasms, it is tempting to speculate that the degree of K-cell activation may play a role in determining the biological behaviour of experimental tumours.…”
mentioning
confidence: 77%
“…Serum collected from rodents with chemical or virus-induced tumours can render normal. lymphoid cells cytotoxic for tumour target cells or increase the cytotoxicity of immune lymphocytes (Pollack, 1973;Ortiz de Landazuri, Kedar and Fahey, 1974;Basham and Currie, 1974). Moreover, passive transfer of cell-dependent antibodies results in significant antitumoral effects in vivo, thus suggesting that ADCC could represent an important antitumoral effector mechanism (Hersey, 1973;Zighelboim, Bonavida and Fahey, 1974).…”
mentioning
confidence: 99%
“…Again, no abrogation of immune lymphocyte cytotoxicity was observed ( Table IV, Experiments of concomitant tumour immunity (Bashford et al, 1908) were performed as other studies reported that the presence of concomitant tumour immunity correlated with the absence of blocking factors (Deekers et al, 1973;Sjogren and Bansal, 1971). 104 H50 cells were injected intradermally in the intrascapular area of 32 hamsters and on the following 4 consecutive weeks groups of Table V indicate that hamsters bearing a primary H50 tumour (palpable-2-0 cm size) showed a heightened resistance and not enhanced growth of a secondary challenge compared with normal controls.…”
Section: W1inn Neutralization Assaymentioning
confidence: 97%
“…Such sera demonstrated characteristics similar to sera taken from animals rendered immune to tumour transplantation by various procedures. These immune sera augmented the cytotoxic reactivity of tumour immune lymphocytes in vitro (potentiation) (Lamon et al, 1974) and also induced normal lymphocytes to specifically kill tumour cells (arming) (Basham and Currie, 1974).…”
Section: Mixed Haemadsorption Testmentioning
confidence: 99%
See 1 more Smart Citation